Linear Regression Analysis between PM2.5 Exposure Levels and Low Birth Weight (LBW) Incidence at Regional General Hospitals in DKI Jakarta - Sri Aisyah Hidayati (CV. Get Press Indonesia, 2025)
Exposure to fine particulate matter (PM2.5) during pregnancy has been associated with an increased risk of low birth weight (LBW), a condition contributing significantly to neonatal morbidity and mortality. Jakarta, as a densely populated metropolitan area, frequently exceeds the World Health Organization (WHO) air quality guidelines, yet local evidence linking PM2.5 exposure to LBW remains limited. This study aims to examine the relationship between maternal exposure to PM2.5 during pregnancy and the incidence of LBW in a public hospital setting in Jakarta. A cross-sectional observational study was conducted among 150 postpartum mothers at a Jakarta public hospital who met inclusion criteria. PM2.5 exposure levels were estimated based on residential location using satellite-calibrated air quality data, while maternal and neonatal data were retrieved from medical records. Data analysis included Pearson correlation, simple linear regression, and multiple linear regression. A significant negative correlation was found between PM2.5 exposure and birth weight (r = -0.476; p < 0.01). Each 1 µg/m³ increase in PM2.5 was associated with a 18.45-gram decrease in birth weight (p < 0.001). In the multiple regression model, PM2.5 remained a significant predictor after adjusting for maternal age, nutritional status, and gestational age, accounting for 51.2% of the variance in birth weight (Adjusted R² = 0.496). Maternal exposure to PM2.5 is a significant risk factor for LBW. Strengthening air pollution control policies is essential to improve maternal and child health outcomes in urban settings like Jakarta.